LIVING LAW DALAM FILSAFAT HUKUM INDONESIA: TELAAH NORMATIF ATAS RELASI HUKUM ADAT, MORAL SOSIAL, DAN HUKUM POSITIF - Muhammad Ikhsan Hattu; Elviandri (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
The concept of living law is a crucial idea in Indonesian legal philosophy, explaining the relationship between customary law, social morality, and positive law. This article aims to analyze living law as a normative reality that exists within society and its role in shaping a just and contextual legal system. The study uses a library research method with a normative-philosophical approach, reviewing literature on law, legal philosophy, and sociology of law relevant to the topic. The findings indicate that living law is inseparable from customary law and social morality that develop within communities. Customary law serves as the primary manifestation because it holds strong legitimacy derived from societal legal awareness. Social morality also plays a critical role in shaping compliance with positive law. The relationship between living law and positive law is dynamic and mutually influential within Indonesia’s pluralistic legal system. Recognition of living law is essential to ensure that national law not only guarantees legal certainty but also reflects substantive justice and societal values.